The brunt of intensive simulation airway management training programme on the final year nursing in one of health training institutions in Sabah - Mazlinda Musa; Fidelia Ferderik Anis; Hamidah Hassan; Syed Sharizman Syed Abdul Rahim; Siti Fatimah Saat (Malaysian Journal of Medicine and Health Sciences, 2020)
Introduction: Airway management is one of the most important steps in emergency patient care, and it is part of the core content of emergency training programme in nursing. Besides, learning in the real clinical area on artificial air¬way management is almost impossible due to the complexity of clinical conditions and non-uniform treatment algo¬rithms that make the training strategies even more difficult to develop. This study was to evaluate the effectiveness of the simulation airway management training programme developed for the final year nursing students. Methods: This was a quasi-experimental with convenience sampling technique approach used. Students were exposed with the Intensive simulation of airway management technique which includes BLS, oropharyngeal measure and insertion, high flow O2 administration, interpret ECG, use of defib and understanding role of arrest team during emergency. The questionnaire on confident level was given before and after the simulation of airway management. Results: The results showed significant different in the mean score of pre-tests and post-tests (CI95% (-0.53414, -0.09586), t= -3.009, df = 19, p<.05), since the probability value (sig. 2-tailed) obtained (.007) is less then predetermine al¬pha value (.05), thus null hypothesis was rejected. Conclusion: Intensive simulation training programme on airway management serves as a bridge on the gap between classroom instruction and the practical application. It acts as a reinforcement strategy on the technical and nontechnical skills to determine their competency the most important thing derived from this study is the increases of students’ sense of security and confidence before they are exposed to real clinical areas. Therefore, this programme is a steppingstone to prepare them to gain on the real experience.